2016
DOI: 10.1007/s13659-016-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA–Topoisomerase I by Acylated Triterpene Saponins from Pittosporum angustifolium Lodd.

Abstract: Previous phytochemical investigation of the leaves and seeds of Pittosporum angustifolium Lodd. led to the isolation and structural elucidation of polyphenols and triterpene saponins. Evaluation for cytotoxicity of isolated saponins revealed that the predominant structural feature for a cytotoxic activity are acyl substituents at the oleanane aglycon backbone. The present work reports the results of a screening of 10 selected acylated saponins for their potential to inhibit the human DNA-topoisomerase I, givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Notable values were also seen in BPF and TKF and GGL. High antioxidative capacity and total phenolic content often dictates the bioactive potential of a plant matrix [ 2 , 4 , 5 ]. Hence, it was postulated that KPF would show high bioactivity in the anticancer and antimicrobial bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…Notable values were also seen in BPF and TKF and GGL. High antioxidative capacity and total phenolic content often dictates the bioactive potential of a plant matrix [ 2 , 4 , 5 ]. Hence, it was postulated that KPF would show high bioactivity in the anticancer and antimicrobial bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…IC 50 values were found to range between 2.8 and 46.5 µM, with most compounds having comparative or higher activities (2.8-8.6 µM) than the positive control camptothecin (7.4 µM). The study revealed the cytotoxic effect was caused only by the inhibition of topoisomerase I [9]. In a blind docking study, all triterpene saponins investigated were expected to display a similar binding mode to camptothecin.…”
Section: Soxhlet Extractive Methodsmentioning
confidence: 99%
“…Bäcker et al [9] further screened the isolated compounds (triterpene saponins) extracted from the Gumby Gumby plant for their cytotoxic potential against tumourigenic cell lines. The authors found evidence of triterpene saponins causing the inhibition of human topoisomerase I in a DNA relaxation assay.…”
Section: Soxhlet Extractive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the retention times of the predominant peaks in the chromatograms of the subfractions (Figure 6), only one peak at a Although numerous studies have identified triterpenoid saponins, terpenoids, phenols, and coumarin compounds isolated from P. angustifolium as having potential anticancer properties [10,17,18,35,36], only a few have been shown to be effective in vitro. Backer et al (2016) screened ten acylated saponins for their ability to inhibit human DNA-topoisomerase I, an enzyme responsible for resolving torsional stress associated with DNA replication, transcription, and chromatin condensation [37]. Inhibitors of DNA-topoisomerase I can inhibit the proliferation of cancer cells, and such agents are commonly used in chemotherapy for their antiproliferative effects.…”
Section: Cytotoxic Activity and Hplc Profilingmentioning
confidence: 99%